Agreement among neurologists on the clinical diagnosis of dystonia at different body sites. Issue 3 (1st March 2003) - Logroscino, G; Livrea, P; Anaclerio, D; Aniello, M S; Benedetto, G; Cazzato, G; Giampietro, L; Manobianca, G; Marra, M; Martino, D; Pannarale, P; Pulimeno, R; et al.
Abstract : Objective: To study the reliability of the diagnosis of blepharospasm, oromandibular dystonia, cervical dystonia, and writer's cramp among neurologists. Methods: 12 patients with adult onset focal segmental dystonia were videotaped in a standardised way. The tape was sent to six neurologists who are involved in clinical practice without a specific interest in movement disorders (general neurologists), and to four neurologists expert in movement disorders. The observers had to recognise whether the patients were affected by dystonia and to distinguish among blepharospasm, oromandibular dystonia, cervical dystonia, and writer's cramp. Interobserver reliability was assessed by κ statistics, and the degree of agreement was classified according to the Landis classification. Results: The 10 neurologists reached slight to moderate agreement on the diagnosis of these four disorders. When the observers were subdivided according with their professional experience in the field, a moderate to perfect agreement on the diagnosis was achieved by specialists in movement disorders, and a fair to moderate agreement by the general neurologists. Conclusions: Neurologists may have different ability to recognise adult onset focal dystonia, depending on their experience and on the type of dystonia.